PROTECTION OF INFORMATION OBJECTS BASED ON RESIDUAL CLASSES - Василенко, В.; Дубчак, О. (Science-based technologies, 2010)
Mechanisms of maintenance of confidentiality, integrity and availability of information streams of telecommuni-cation networks are considered; the noiseproof code on the basis of conditional classes is presented as a basis of methods of information safety.